The Role Of Lycopene to Nuclear Factor Kappa Beta (Nf-κB) Activities and Intracellular Cell Adhesion Molecule-1 (Icam-1) Expressions on Leptin-Induced Endothelial Cell - Heni Fatmawati; S Satuman; Endang SW; A Rudijanto; M Rasjad Indra (Jurnal ILMU DASAR, 2010)
There is adipocytokine dysregulation on obesity such as amplified leptin, and reduced adiponectin at serum levels . Leptin has been proved to increase oxidative stress in endothelial cell. The adipocyte functions as an important secretory organ via nuclear factor-κ B (NF-κB) releasing a number of bioactive molecules such as leptin. Lycopene, an antioxidant, is presumed having the ability to block the atherogenesis mechanism, which is stimulated a proinflamatory cytokine and adhesion molecules ICAM-1 by NF-κB. Therefore, the aim of this research was to prove and to determine whether lycopene could decrease the NF-κBandICAM-1 expressionin Human Umbillical Vein Endothelial Cells (HUVECs) culture induced by 500 ng/mL leptin. In vitro study used primary culture of the HUVECs were devided in to 7 groups, there were (1) 0 ng/mL leptin and 0 μM lycopene, (2) induced by 500 ng/mL leptin for 12 hours, (3) induced by leptin and lycopene with concentration 10; 25; 40; 55 and 75 μM for 12 hours. Then the identification of NF-κB was applied by using imunocytochemistry compared with ELISA procedure on cell endothel culture lysate and ICAM-1 expression was measured by using RT PCR. It was showed that lycopene 25 μM decreased NF-κB level and ICAM-1 expression significantly in Human Umbillical Vein Endothelial Cells (HUVECs) culture induced by leptin 500 ng/mL.Leptin was increased NF-κB and ICAM-1 expression in HUVECs culture and was decreased by lycopene. Optimum dose of lycopene is 25 μM.